Using end buckles to improve debonding resistance in FRP-bonded precracked RC beams. Issue 1 (January 2023) - Zhou, Chao-Yang; Chen, Heng-Yi; Wang, Yi; He, Xue-Jun
The strengthening effect of reinforced concrete (RC) members externally bonded (EB) with fiber reinforced polymer (FRP) laminates is significantly affected by interfacial debonding failure. To improve the connection between FRP sheets and concrete, a novel type of anchor device for FRP sheets called buckle was proposed in this study. This device can effectively lock the end of the sheet using a patented method of wrapping. In addition to conventional external bonding, bolts were installed on the buckles to form hybrid anchored (HA) FRP sheet. To verify the effectiveness of this new method, a precracked RC beam was prepared in comparison with two undamaged beams strengthened with EB or HA FRP sheets. As observed, end buckles can limit the development of cracks regardless of initial cracking. Despite the occurrence of intermediate debonding due to initial cracks, both the ultimate capacity and failure ductility were significantly improved. Owing to the end buckles, the debonding resistance was excellent, and the initial cracking of the beam hardly affected the strengthening effect. In addition, existing formulas were used to calculate the lower limit of the ultimate load of the specimen strengthened with HA FRP, which was still higher than that of the specimen strengthened by EB FRP. Therefore, the results confirmed that the debonding resistance was greatly enhanced due to the locking of the FRP sheet via end buckles, and the proposed method is useful to guarantee the strengthening effect.